2016
DOI: 10.1021/jacs.6b00541
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)-Chromodorolide B

Abstract: The first total synthesis of a chromodorolide diterpenoid is described. The synthesis features a bimolecular radical addition/cyclization/fragmentation cascade that unites butenolide and trans-hydrindane fragments while fashioning two C–C bonds and stereoselectively forming three of the ten contiguous stereocenters of chromodorolide B

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 36 publications
1
34
0
3
Order By: Relevance
“…The obtained electrocatalysts exist in the form of rutile-anatase TiO 2 /RGO nanocomposites in which the components of rutile and anatase can be tuned. Benefit from lower activation energy induced by the charge transfer between anatase and rutile, as well as TiO 2 and RGO, the optimized sample exhibits an overpotential as low as 283 mV at 10 mA cm À2 in 1 M KOH, which is superior to the reported TiO 2 (600 mV) [10] and comparable with the leading results of other active materials. [2d,i,j,3d,4a-c,5b-d,6a,10] The fabrication of the rutileanatase/RGO nanocomposites with enhanced OER catalytic activity along with its mechanism investigation may offer a new alternative way for potential electrocatalysts.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…The obtained electrocatalysts exist in the form of rutile-anatase TiO 2 /RGO nanocomposites in which the components of rutile and anatase can be tuned. Benefit from lower activation energy induced by the charge transfer between anatase and rutile, as well as TiO 2 and RGO, the optimized sample exhibits an overpotential as low as 283 mV at 10 mA cm À2 in 1 M KOH, which is superior to the reported TiO 2 (600 mV) [10] and comparable with the leading results of other active materials. [2d,i,j,3d,4a-c,5b-d,6a,10] The fabrication of the rutileanatase/RGO nanocomposites with enhanced OER catalytic activity along with its mechanism investigation may offer a new alternative way for potential electrocatalysts.…”
Section: Introductionsupporting
confidence: 52%
“…Recently, TiO 2 has been reported to catalyze OER via surface modifications. [10] In detail, the OER activity of TiO 2 can be enhanced by inducing oxygen vacancy defects while it still exhibits a high overpotential of 600 mV at 10 mA cm À2 . [10] So, if we can fabricate an efficient TiO 2 electrocatalyst with a low overpotential, it will be of great significance for the design of electrocatalysts.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Having confirmed that trisubstituted acetonide radicals in this series react with butenolide 4 preferentially in a syn fashion, which is required for the synthesis of (−)-chromodorolide B ( 3 ), [4] we turned to examine structurally more elaborate substrates that harbored the trimethylhydrindane fragment found in 3 (Table 2). Because of the scarcity of the more elaborate radical precursors in this series and limited solubility of diol carboxylic acid precursor 8c , the coupling reactions reported in Tables 1 and 2 were performed under identical conditions at a concentration of 0.1 M in DME.…”
mentioning
confidence: 99%
“…It should be recognized that a higher reaction concentration typically improves the yield of bimolecular radical coupling reactions of this type. [4,5] For example, carrying out the coupling reactions of precursors 5c and 8e at 0.4 M instead of 0.1 M increased the yield of the coupled products by more than 30%.…”
mentioning
confidence: 99%